ALI Analysis Guarantee Law On State Civil Apparatus Decree As A Basis Of Guarantee For Banking Credit Application: Analysis Guarantee Law On State Civil Apparatus Decree As A Basis Of Guarantee For Banking Credit Application - Mohamad Ali (Jurnal Hukum Lex Generalis, 2024)
That the current economic conditions and development in Indonesia cannot be separated from the role and function of existing banking, because banking is a "financial medium." Therefore, banking functions as a distributor and collector of budgets for the community and plays a supporting role in the implementation of development at the regional and national levels in order to foster equitable development and its impact on society, national stability and economic development as well as aspects of improving the quality of life of many people. Among all banking activities, one of them is providing credit to people who apply for credit, including the Nagara Civil Apparatus (ASN). This writing aims to find out and understand the classification of ASN SKs that are used to apply for credit guarantees from banks and how they are viewed from a legal guarantee perspective. This writing uses normative methods juridical method using secondary data sources such as loan agreements, guarantee laws related to banking credit, laws and regulations related to civil law, literature, journals and previous research results and is supported by primary data at the Serang City Government Office. in this case the Walantaka District Office.